2022
DOI: 10.3389/fcvm.2022.827231
|View full text |Cite
|
Sign up to set email alerts
|

A Left Ventricular Mechanical Dyssynchrony-Based Nomogram for Predicting Major Adverse Cardiac Events Risk in Patients With Ischemia and No Obstructive Coronary Artery Disease

Abstract: BackgroundThe risk stratification of patients with ischemia and no obstructive coronary artery disease (INOCA) remains suboptimal. This study aims to establish a left ventricular mechanical dyssynchrony (LVMD)-based nomogram to improve the present situation.MethodsPatients with suspected coronary artery disease (CAD) were retrospectively enrolled and divided into three groups: normal (stenosis <50%, without myocardial ischemia), INOCA (stenosis <50%, summed stress score >4, summed differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Similar results were reported by Mannarino et al [ 27 ], wherein the analysis of regional perfusion abnormalities on CZT SPECT was predictive of MACEs in a large population of patients with suspected CAD. Furthermore, our previous study demonstrated that the left ventricular mechanical dyssynchrony (LVMD) evaluated by the CZT SPECT phase analysis technique allows for better risk stratification of INOCA patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Mannarino et al [ 27 ], wherein the analysis of regional perfusion abnormalities on CZT SPECT was predictive of MACEs in a large population of patients with suspected CAD. Furthermore, our previous study demonstrated that the left ventricular mechanical dyssynchrony (LVMD) evaluated by the CZT SPECT phase analysis technique allows for better risk stratification of INOCA patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Також було показано, що ДМ є предиктором подій в короткому періоді спостереження у хворих після аортокоронарного шунтування [15]. Крім того, аналіз Каплана -Майєра виявив значно вищу частоту великих несприятливих серцево-судинних подій у пацієнтів з необструктивною коронарною хворобою серця та ДМ порівняно з хворими без дисинхронії [16].…”
Section: вступunclassified